From Content to Obligation: Adapting Zakat Law for Digital Creators - Dodon Alfiander; Firdaus Firdaus; Zainal Azwar; Arifki Budia Warman; Iswandi Iswandi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
The development of information technology today has made the social media platforms YouTube and Instagram very popular and has given birth to many YouTuber and Celebgram content creators. Content creators use this social media platform as a means to earn income with fantastic financial value of up to hundreds of millions, even billions of rupiah every month. This article aims to discuss zakat for YouTubers and Celebgrams. By using the library research method with a normative approach, this article provides answers to the issue of zakat for YouTubers and Celebgrams. This article concludes that: First, Yusuf al-Qardhawi views income YouTubers and Celebgram is included in al-mâl al-mustafâd, and must be given zakat. Second, there are differences of opinion as to whether zakat is paid to gold and silver zakat, or agricultural zakat. Yusuf al-Qardhawi in one condition qiyas the provisions of agricultural zakat. In other conditions, if the nisab is not met then zakat is paid to gold and silver. Meanwhile, based on MUI Fatwa No. 3 of 2003 concerning Income Zakat, reinforced by MUI Fatwa No. 04 of 2024 concerning Zakat for YouTubers, Celebrities, and Other Digital Creative Economy Actors, its implementation is subject to zakat on gold and silver. Al-Qardhawi's opinion and the provisions contained in the MUI Fatwa, provide an answer to the need to determine zakat law for the income of YouTubers and Instagram celebrities, as part of the dynamic development of information technology which has resulted in the development of contemporary law in the field of zakat. Perkembangan teknologi informasi saat ini menjadikan platform media sosial YouTube dan Instagram menjadi sangat diminati dan melahirkan banyak pelaku konten kreator YouTuber dan Selebgram. Pelaku konten kreator menjadikan platform media sosial ini sebagai sarana untuk meraup penghasilan dengan nilai finansial yang fantastis hingga mencapai ratusan juta, bahkan milyaran rupiah setiap bulannya. Artikel ini bertujuan untuk mendiskusikan zakat bagi YouTuber dan Selebgram. Dengan menggunakan metode library research dengan pendekatan normatif, artikel ini memberikan jawaban terhadap persoalan zakat bagi YouTuber dan Selebgram. Artikel ini menyimpulkan bahwa: Pertama, Yusuf al-Qardhawi memandang pengasilan YouTuber dan Selebgram termasuk dalam al-mâl al-mustafâd, dan wajib untuk dizakatkan. Kedua, terdapat perbedaan pendapat apakah penunaian zakatnya diqiyaskan kepada zakat emas dan perak, atau zakat pertanian. Yusuf al-Qardhawi pada satu kondisi meng-qiyaskan pada ketentuan zakat pertanian. Pada kondisi lain, jika nisabnya tidak terpenuhi maka diqiyaskan kepada zakat emas dan perak. Sementara, berdasarkan Fatwa MUI No. 3 Tahun 2003 tentang Zakat Penghasilan, diperkuat dengan Fatwa MUI No. 04 Tahun 2024 tentang Zakat YouTuber, Selebgram, dan Pelaku Ekonomi Kreatif Digital Lainnya, pelaksanaanya diqiyaskan kepada zakat emas dan perak. Pendapat al-Qardhawi serta ketentuan yang termuat pada Fatwa MUI, memberikan jawaban terhadap kebutuhan penetapan hukum zakat bagi penghasilan YouTuber dan Selebgram, sebagai bahagian dari dinamika perkembangan teknologi informasi yang berakibat pada perkembangan hukum kontemporer dalam bidang zakat.